TRANSLATION CHALLENGES OF EMOTIVE VERBS BETWEEN ENGLISH AND UZBEK - Kurvonbekov Manuchekhr Islomjon ugli (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Annotation: This article examines translation challenges of emotive verbs between English and Uzbek. It focuses on linguistic, cultural, and pragmatic difficulties that arise during translation. The study highlights the importance of cultural awareness and translation strategies in achieving accurate emotional and semantic equivalence between the two languages.
Keywords: Key Words: Emotive verbs, translation challenges, English language, Uzbek language, cultural influence, semantic equivalence, pragmatics